(untitled) (RevSALUS - Revista Científica Internacional da Rede Académica das Ciências da Saúde da Lusofonia, 2025)
Psychedelic compounds, including psilocybin, psilocin, lysergic acid diethylamide (LSD), 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT), and mescaline, have long been recognized for their recreational effects and involvement in forensic cases. They have recently gained attention also for their potential therapeutic applications in treating neurological and psychiatric disorders [1]. Despite this growing interest, the toxicological profiles of these substances—particularly their neurotoxic effects and underlying mechanisms—are not well understood. It is crucial to investigate the safety and potential neuroprotective/neurotoxic properties of these compounds to evaluate their role in both therapeutic contexts and forensic investigations. This study utilized the SH-SY5Y human neuroblastoma cell line to evaluate the cytotoxicity of these compounds through mitochondrial and lysosomal integrity assays (MTT and Neutral Red, NR).SH-SY5Y cells were cultured under standard conditions and treated with increasing concentrations of each compound for 48h to determine concentration-dependent toxicity [6 x 10-6 – 0.5 mM for psilocybin (n=22 concentrations); 1.3 x 10-5 – 1.5 mM for psilocin (n=16) and LSD (n=16); and 1.3 x 10-5 – 2.0 mM for 5-MeO-DMT (n=32) and mescaline (n=39)]. MTT and NR uptake assays were employed to evaluate cellular viability (minimum of seven independent experiments). Additionally, a neuroprotection study was conducted to assess the potential protective effects of the psychedelic compounds against glutamate-induced toxicity. SH-SY5Y cells were pre-treated with sub-toxic concentrations of each psychedelic compound, followed by exposure to glutamate. Viability was then assessed after 48h using the MTT assay to determine whether any of the psychedelics exhibited protective properties under excitotoxic conditions (five independent experiments). Data were analysed using GraphPad Prism software and fitted according to the Logit model to determine EC 50. Results were also presented as mean ± standard error of the mean. Statistical comparisons between groups were done using the Kruskal-Wallis test, followed by Dunn’s multiple comparison test.The concentration-response results from MTT and NR assays revealed distinct neurotoxicity profiles across the psychedelic compounds. Psilocybin did not reach an EC50 within the tested concentration range, suggesting minimal or no significant toxicity under the assay conditions. Psilocin exhibited moderate cytotoxicity, with EC50 values of 0.42 mM (MTT) and 0.69 mM (NR), indicating that it reduced cell viability at relatively lower concentrations than psilocybin. LSD showed the highest cytotoxicity among the tested compounds, with EC50 values of 0.23 mM (MTT) and 0.57 mM (NR), suggesting substantial effects on both mitochondrial activity and lysosomal integrity at lower concentrations. 5-MeO-DMT and mescaline demonstrated comparatively lower toxicity, with higher EC50 values in both assays (1.17–1.69 mM), indicating that these compounds affected cell viability only at higher concentrations. Concerning their neuroprotective potential, pre-treatment with these compounds did not significantly mitigate glutamate-induced toxicity, indicating limited neuroprotective effects.These findings suggest that psychedelics exhibit differential neurotoxicity profiles in SH-SY5Y cells, with LSD and psilocin showing higher neurotoxic potency compared to psilocybin, 5-MeO-DMT, and mescaline, making them comparatively safer under the conditions tested. However, pre-treatment with these compounds did not significantly mitigate glutamate-induced toxicity, indicating limited neuroprotective potential in this model. In future studies, we intend to clarify the mechanisms responsible for their cytotoxicity.